2022
DOI: 10.1111/jcpe.13629
|View full text |Cite
|
Sign up to set email alerts
|

Pasteurized Akkermansia muciniphila reduces periodontal and systemic inflammation induced by Porphyromonas gingivalis in lean and obese mice

Abstract: Aim:The aim of this study was to evaluate the effect of the administration of pasteurized Akkermansia muciniphila and Amuc_1100 on periodontal destruction in lean and obese mice and to determine the impact of the mode of administration.Materials and Methods: Porphyromonas gingivalis-associated experimental periodontitis was induced in lean and obese mice. After 3 weeks, live, pasteurized A. muciniphila or Amuc_1100 was administered by oral or gastric gavage for three additional weeks. Moreover, an evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Recently, pasteurized Akk has been shown to alleviate Porphyromonas gingivalis -induced periodontitis. In a study by Mulhall et al in lean and obese mice, P. gingivalis -associated periodontitis was induced by oral or gavage administration of live Akk (10^9), pasteurized Akk (10^9), and the Akk outer membrane protein Amuc_1100 (6 ug/mouse) for 3 weeks [ 60 ]. The results showed that live Akk bacteria, pasteurized Akk, and Amuc_1100 significantly reduced P. gingivalis -induced periodontal injury and inflammatory infiltration, decreased plasma TNF-α levels, and increased IL10 levels.…”
Section: Recent Pre-clinical and Clinical Postbiotic Studiesmentioning
confidence: 99%
“…Recently, pasteurized Akk has been shown to alleviate Porphyromonas gingivalis -induced periodontitis. In a study by Mulhall et al in lean and obese mice, P. gingivalis -associated periodontitis was induced by oral or gavage administration of live Akk (10^9), pasteurized Akk (10^9), and the Akk outer membrane protein Amuc_1100 (6 ug/mouse) for 3 weeks [ 60 ]. The results showed that live Akk bacteria, pasteurized Akk, and Amuc_1100 significantly reduced P. gingivalis -induced periodontal injury and inflammatory infiltration, decreased plasma TNF-α levels, and increased IL10 levels.…”
Section: Recent Pre-clinical and Clinical Postbiotic Studiesmentioning
confidence: 99%
“…On the other hand, they can also enhance oral tolerance and prevent food allergy [ 96 ]. Experiments in mice have demonstrated that Akkermansia muciniphila helps to reduce TNF-α plasma levels and increase IL-10 in mice after pasteurization [ 97 ]. Clinical trials have demonstrated sublingual immunotherapy’s safety and clinical efficacy with heat-inactivated bacteria (MV130) for preventing respiratory tract infections [ 95 ].…”
Section: Postbiotics and Food Allergymentioning
confidence: 99%
“…Porphyromonas gingivalis 36 , suggesting that the addition of probiotics might be another effective channel of treatment.…”
Section: Pasteurized Akkermansia Muciniphila Reduced Periodontal and ...mentioning
confidence: 99%